2020
DOI: 10.5664/jcsm.8380
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism in patients with obstructive sleep apnea: frequency, hospital outcomes, and recurrence

Abstract: Study Objectives: The objectives of this study were to assess the effect of obstructive sleep apnea (OSA) on the risk of acute pulmonary embolism (PE), hospital outcomes including mortality, and PE recurrence. Methods: We retrospectively enrolled adult patients, admitted to Mayo Clinic Hospital in Rochester, Minnesota, within a 5-year period (2009)(2010)(2011)(2012)(2013). We compared frequency of PE, hospital mortality, and secondary outcomes in patients with OSA versus patients without OSA. We assessed risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…After evaluation of full-texts 11 were excluded as they did not satisfy the inclusion criteria. Finally, 12 studies were included in the present review (8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…After evaluation of full-texts 11 were excluded as they did not satisfy the inclusion criteria. Finally, 12 studies were included in the present review (8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…This finding was not reported in any other study that was analyzed in this review. Seckin et al found that patients with OSA who were treated with positive airway pressure (PAP) therapy had a 30% reduction in the relative risk for PE recurrence; however, this result was not statistically significant, possibly due to the small sample size of the subcohort [89]. A higher risk of recurrent VTE was reported in patients who are poorly compliant with CPAP therapy [69].…”
Section: Reviewmentioning
confidence: 99%
“…A different trial involving over 25 000 participants concluded that risk of acute pulmonary embolism (PE) occurrence and recurrence is significantly elevated with OSA compared with those without. 367 Treatment for OSA might have a modifying effect on PE occurrence.…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%
“…Another study explored the impact of OSA on the risk of acute pulmonary embolism, hospital outcomes including mortality, and PE recurrence. 367 Adult patients from a single hospital system (Mayo Clinic, Rochester, Minn) were retrospectively enrolled over a 5year period. Frequency of PE, hospital mortality, and secondary outcomes were evaluated in participants with versus without OSA.…”
Section: Pathophysiology and Medical Implicationsmentioning
confidence: 99%